Restorative justice's applicability in the Alberta child welfare system - Gagnon, Alexandra (My University, 2021)
Many criticisms have been made about Child Services failing to protect children (Pennell & Burford, 2000). Alberta Child Services must address these criticisms to ensure that all individuals impacted by the harms receive the care and treatment they require. The paper argues that the principles of restorative justice would benefit Child Services in Alberta, and that these principles should be implemented within the Alberta Child Services System.
Keywords: Alberta Child Services; restorative justice